PEMBERDAYAAN MASYARAKAT MELALUI SOSIALISASI DAN EDUKASI HOLISTIK: LITERASI KEUANGAN, PEDULI LINGKUNGAN DAN MARAKNYA BULLYING DI DESA JUNGKAT - Rahsia, Shandra Andina (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) was conducted to enhance the capacity of the local community in Jungkat Village, Jongkat District, Mempawah Regency through a holistic educational approach encompassing financial literacy, environmental awareness, and bullying prevention. The one-month program employed participatory methods such as socialization, counseling, group discussions, and hands-on practice. The financial literacy activities focused on household and small business financial management, environmental education emphasized waste segregation and reforestation, while anti-bullying campaigns targeted children and adolescents to foster a healthier social environment. Evaluation results indicated improved community understanding of basic financial management, greater awareness of environmental cleanliness, and stronger attitudes among youth toward addressing bullying issues. This KKN program not only provided short-term educational impacts but also encouraged the formation of sustainable positive behaviors that contribute to building a more independent, empowered, and harmonious community in Jungkat Village.